A Novel AuNP‐Based Glucose Oxidase Mimic with Enhanced Activity and Selectivity Constructed by Molecular Imprinting and O2‐Containing Nanoemulsion Embedding. Issue 22 (12th September 2018) - Fan, Lin; Lou, Doudou; Wu, Haoan; Zhang, Xizhi; Zhu, Yefei; Gu, Ning; Zhang, Yu
Abstract: In spite of the competitive advantages, inorganic nanoparticle mimic enzymes exhibit inherent disadvantages of limited catalytic efficiency and lacking selectivity. Here, a gold nanoparticle (AuNP)‐based mimic enzyme with significantly enhanced glucose selectivity and catalytic activity is constructed and demonstrated for the first time. Aminophenylboronic acid is employed to increase the affinity to glucose, as well as build molecular imprinted polymer shells to realize the selectivity for template molecules of glucose. Besides that, heptadecafluoro‐ n ‐octyl bromide nanoemulsion with the function of providing oxygen is introduced to gain a further improvement in catalytic activity, which successfully enhances the catalytic efficiency ( k cat / K m ) up to about 270‐fold. Based on the demonstrated catalytic properties, AuNP‐based glucose oxidase mimics are successfully applied in practical glucose detection of drinks and blood glucose. Abstract : Gold nanoparticle‐based enzyme mimics with selectivity and applicability in practical glucose detection of drinks and blood glucose are constructed by combining adjacent hydroxyls‐bindable aminophenylboronic acid and molecular imprinting technology. This leads to 270‐fold enhanced catalytic efficiency ( k cat / K m ) by increasing the substrate affinity and introducing heptadecafluoro‐ n ‐octyl bromide nanoemulsion as an oxygen donor at the same time.